#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.

Click to Chat

1800-1023-196

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# if cos^4A-sin^4A=x, find cos^6A-sin^6A in terms of x

## 2 Answers

10 years ago

cos^4 A - sin^4 A = x

= (cos^2 A)^2 - (sin^2 A)^2 = (cos^2 A + sin^2 A)(cos^2 A - sin^2 A) = x

==> cos^2 A - sin^2 A = x

cos^6 A - sin^6 A = (cos^2 A)^3 - (sin^2 A)^3 = (cos^2 A - sin^2 A)(cos^4 A + sin^4 A + sin^2 A. cos^2 A)

= x . ( 1 + sin^2 A .cos^2 A)

= x + x.sin^2 A.cos^2 A

Please approve !

10 years ago

cos4A-sin4A = (cos2A+sin2A)(cos2A-sin2A) = x

= (cos2A-sin2A) = x                                                 (cos2A-sin2A = cos2A)

cos2A = x      ..........1

sin2A = (1-x2)1/2   ............2

we have to find the value of cos6A - sin6A = P

P = cos6A - sin6A

=(cos2A+sin2A)(cos4A + sin4A-cosAsinA)

=(sin4A+cos4A-cosAsinA)

= [ 1 + cos22A -sin2A]/2

= [ 1+ x2 - (1-x2)1/2]/2

this is the value of expression

## ASK QUESTION

Get your questions answered by the expert for free